Crowdsourcing Knowledge: An Extension Approach for Remunerative and Sustainable Home Garden Farming Systems in Kerala - Thomas, Allan; Babu, M. Nithish (Journal of Extension Education, 2020)
Kerala has pioneered development models through farmer participatory approaches. Involving the grassroots in scientific studies can help improve crop variety adoption and refined technology recommendations. Participatory tools like Participatory Rural Appraisal (PRA), Participatory Technology Development (PTD), On Farm Testing (OFT), Front Line Demonstrations (FLD) and Participatory Breeding Programmes (PBP) are all time-tested examples of its successful use in researches. Crowdsourced citizen science approach called tricot – ‘triadic comparisons of technologies’ is popular today, where farmers are made to adopt three crop varieties or technologies randomly assigned to them from a broader set of varieties/technologies for final choice aimed at continuous adoption. The results of this study conducted during 2019-2020 revealed that more than 80% of the farmers fully adopted the technology prescribed in the checklist as a result of crowdsourcing knowledge. The results on attitude of farmers towards crowdsourcing revealed that majority of the farmers posessed favourable attitude towards crowdsourcing approach.